Endovascular Embolization of Spontaneous Iliopsoas Hematoma: First Experience with Squidperi. (27th February 2018) - Torcia, Pierluca; Squarza, Silvia; Rossi, Umberto G.; Rigamonti, Paolo; Pescatori, Lorenzo Carlo; Damiani, Giovanni; Cariati, Maurizio
Abstract : A 79-year-old man, suffering from atrial fibrillation and on anticoagulation therapy, was admitted at the emergency department of our institution because of a worsening respiratory insufficiency. After a diagnostic work-up, he was found to suffer from pneumonia, and antibiotic therapy was settled. He was kept under observation for his pulmonary conditions but, within a week, he developed a spontaneous iliopsoas hematoma, due to a sudden dysregulation of anticoagulation therapy subsequent to new in-hospital treatments. An endovascular approach was attempted and the bleeding vessels were embolized with a new liquid agent, named Squidperi (Emboflu, Switzerland). Complete exclusion of the diseased vessels was obtained and no complications occurred after the procedure. We conclude that Squidperi can be considered as an option for treatment of spontaneous iliopsoas hematomas.